(untitled) (Research, Society and Development, 2020)
The purpose of this article is to investigate the origins and development of environmental auditing as a key management technique and as a self-regulatory tool that is believed to have arisen in response to increased public and business awareness of environmental issues. Studies focused on the characterization of environmental auditing, the relationship between environmental auditing and accounting and how to do an environmental audit pointed out as a result that one of the ways in which companies demonstrate their commitment to the environmental issue is to include, in the system management environmental, environmental auditing techniques that use environmental accounting as an adequate tool for measuring the environmental performance of companies, correcting distortions and improving control in reducing environmental and patrimonial impacts on organizations. To support the theoretical framework, it was used in a conceptual way, the benchmarks defined by industry experts and with this we can demonstrate how the audit is of paramount importance for the environmental management of an organization. We define environmental auditing as a tool in which it helps the organization to carry out the qualification and licensure of technical qualifications efficiently and effectively. It was found that the process requires a nominated person, the lead auditor and carried out by the others, always seeking to assess performance, legal compliance, and commitment to the organization of a company’s environmental policies. Business obligations to the environment are of paramount importance for analyzing functions, ensuring awareness of their environment, employees, society and the like, so that we have the prevention and preservation of the environment and the natural resources in it.